Dampak Dana Pihak Ketiga dan Penyaluran Kredit Terhadap Profitabilitas Perbankan - Khaerunisahadi, Adisti Ayuningtyas (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2023)
This study analyzes the effect of third-party funds and lending on the profitability of PT. Bank Woori Saudara 1906, Tbk Sukabumi branch. The variables used in this study were third-party funds, credit distribution, and bank profitability. The sample used is the quarterly financial statements at PT. Bank Woori Saudara 1906, Tbk Sukabumi branch with the period 2009-2016, the number of samples in this study is 32 samples, which can be included in the data processing. Data analysis using SPSS program version 24. The statistical method used to test hypotheses is multiple linear regression analysis. Upon analysis, it was found that some showed that third-party funds had no effect on ROA, credit distribution had an effect on ROA, and simultaneously third-party funds and credit distribution had an effect on ROA. The coefficient of determination shows the influence of third-party funds and credit distribution on ROA by 77.7% and the remaining 22.3% is influenced by other factors.